Self-Motivation Strategies: The Quality of Internal Dialogue Is Important for Well-Being and Academic Success - Gordeeva T.O; Sychev O.A (Moscow State University of Psychology and Education, 2021)
The study, carried out on a large sample of students (N=820) during the period of forced online learning, made it possible to study the phenomenon of self-moti¬vation of educational activity, and the relationship of its different types with academic success and well-being. The results concerning subjective well-being are largely consistent with the data recently obtained by K. Sheldon and colleagues on American samples, and testify in favor of the importance of internal dialogue with oneself, based on the support of one's own autonomy. In addition, with the help of structural equation modeling, it was shown that motives of learning activ¬ity are a partial mediator of these relations. Thus, the autonomous strategy of self-motivation is a predictor of the success of students' learning activities, and this connection is partially mediated by another important source of well-being - the autonomous motivation, represented by internal and identified motivation. On the contrary, a controlled strategy of self-motivation, which presupposes a rigid ("oppressive") style of self-motivation, was a predictor of the presence of con¬trolled academic motivation, amotivation and an inverse predictor of subjective well-being.